Penerapan Keterampilan Mengajar Guru, Praktik Keagamaan, dan Kemandirian terhadap Hasil Belajar Pendidikan Agama Islam di MTsN 2 Kota Surabaya - Yulianto, Agus; Masnawati, Eli; Darmawan, Didit (Jurnal Kependidikan, 2024)
Abstract - The quality of Islamic Religious Education teaching is influenced by the understanding of Islamic teachings in everyday life and its application. For this reason, this research aims to analyze the influence of teachers' basic teaching skills and students' religious practices on Islamic Religious Education learning outcomes at Madrasah Tsanawiyah Negeri 2 Surabaya City. Islamic Religious Education plays an important role in shaping the student’s character and morals so that the quality of Islamic Religious Education teaching becomes a determining factor in achieving the goals of religious education. The factors studied include teachers' basic teaching abilities, religious practices, and student independence. This research used a quantitative approach with 100 students from class VII. Data collection was carried out through questionnaires and regression analysis which was used to assess the influence of independent variables on Islamic Religious Education learning outcomes. Research shows that the teachers' basic teaching skills, religious practices, and student independence partially and simultaneously have a positive effect on Islamic Religious Education learning outcomes. These results show that teachers' basic teaching skills, which include the ability to convey material, mastery of teaching methods, and the ability to adapt to students' needs, have a positive impact on students' understanding of religious teachings. Students' religious practices include religious activities such as prayer, reading the Quran, and other religious practices. The intrinsic attitude value which will lead to independence in learning and teaching religious teachings personally in everyday life makes a positive contribution to the learning outcomes of Islamic religious education.